Carbon economy of Mediterranean seagrasses in response to thermal stress. (October 2018) - Marín-Guirao, L.; Bernardeau-Esteller, J.; García-Muñoz, R.; Ramos, A.; Ontoria, Y.; Romero, J.; Pérez, M.; Ruiz, J.M.; Procaccini, G.
Abstract: Increased plant mortality in temperate seagrass populations has been recently observed after summer heatwaves, although the underlying causes of plant death are yet unknown. The potential energetic constrains resulting from anomalous thermal events could be the reason that triggered seagrass mortality, as demonstrated for benthic invertebrates. To test this hypothesis, the carbon balance of Posidonia oceanica and Cymodocea nodosa plants from contrasting thermal environments was investigated during a simulated heatwave, by analyzing their photosynthetic performance, carbon balance (ratio photosynthesis:respiration), carbohydrates content, growth and mortality. Both species were able to overcome and recover from the thermal stress produced by the six-week exposure to temperatures 4 °C above mean summer levels, albeit plants from cold waters were more sensitive to warming than plants from warm waters as reflected by their inability to maintain their P:R ratio unaltered. The strategies through which plants tend to preserve their energetic status varied depending on the biology of the species and the thermal origin of plants. These included respiratory homeostasis ( P. oceanica warm-plants), carbon diversion from growth to respiration ( C. nodosa cold-plants) or storage ( P. oceanica warm-plants) and changes in biomass allocation ( C. nodosa warm-plants). Findings suggest an important geographic heterogeneity in the overall response of Mediterranean seagrasses to warming with potential negative impacts on the functions and services offered by seagrass meadows including among others their capacity for carbon sequestration and carbon export to adjacent ecosystems. Graphical abstract: Highlights: Mediterranean seagrasses resist the thermal effects during a simulated heatwave. Sensitivity to warming was higher in plants from cold thermal environments. The ability to tune the plant carbon balance determines the acclimation capacity. To keep energy reserves plants divert carbon from growth to respiration or storage. Plants also achieve respiratory homeostasis or modify biomass allocation.